Трубопроводный транспорт нефти и нефтепродуктов: справочное пособие; в 2 т. - Мастобаев Б. Н. Борис Николаевич; Нечваль А. М. Андрей Михайлович; Гареев М. М. Мурсалим Мухутдинович; Дмитриева Т. В. Татьяна Владимировна; Валеев А. Р. Анвар Рашитович; Лисин Ю. В. (Москва, Недра, 2017)
Авт. указ. на обороте тит. л.